Fresh or frozen day 6 blastocyst transfer: is there still a question? - Lucile Ferreux; Mathilde Bourdon; Ahmed Chargui; Julie Firmin; Chloé Maignien; Pietro Santulli; Catherine Patrat; Khaled Pocate-Cheriet (BMC, 2024)
Abstract Background The Live Birth Rate (LBR) after day 5 (D5) blastocyst transfer is significantly higher than that with D6 embryos in both fresh and frozen-vitrified embryo transfer cycles, according to the most recently published meta-analyses. Therefore, for women obtaining only D6 blastocysts, the chances of pregnancy may be lower but nonetheless sufficient to warrant transferring such embryos. The best strategy for transfer (i.e., in fresh versus frozen cycles) remains unclear and there is a paucity of data on this subject. Methods A total of 896 couples with D6 single blastocyst transfers were retrospectively analyzed: patients receiving a fresh D6 embryo transfer (Fresh D6 transfer group, n = 109) versus those receiving a frozen-thawed D6 embryo transfer (Frozen D6 transfer group, n = 787). A subgroup comprising a freeze-all cycle without any previous fresh or frozen D5 embryo transfers (Elective frozen D6, n = 77) was considered and also compared with the Fresh D6 transfer group. We compared LBR between these two groups. Correlation between D6 blastocyst morphology according to Gardner's classification and live birth occurrence was also evaluated. Statistical analysis was carried out using univariate and multivariate logistic regression models. Results The LBR was significantly lower after a fresh D6 blastocyst transfer compared to the LBR with a frozen-thawed D6 blastocyst transfer [5.5% (6/109) vs. 12.5% (98/787), p = 0.034]. Comparison between LBR after Elective frozen D6 group to the Fresh D6 blastocyst transfers confirmed the superiority of frozen D6 blastocyst transfers. Statistical analysis of the blastocyst morphology parameters showed that both trophectoderm (TE) and inner cell mass (ICM) grades were significantly associated with the LBR after D6 embryo transfer (p < 0.001, p = 0.037). Multiple logistic regression revealed that frozen D6 thawed transfer was independently associated with a higher LBR compared with fresh D6 transfer (OR = 2.54; 95% CI: [1.05-6.17]; p = 0.038). Our results also show that transferring a good or top-quality D6 blastocyst increased the chances of a live birth by more than threefold. Conclusions Our results indicate that transferring D6 blastocysts in frozen cycles improves the LBR, making it the best embryo transfer strategy for these slow-growing embryos. Clinical trial number Not applicable.